2020
DOI: 10.48550/arxiv.2010.03695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serendipitous Discovery of Nine White Dwarfs With Gaseous Debris Disks

Carl Melis,
B. Klein,
A. E. Doyle
et al.

Abstract: Optical spectroscopic observations of white dwarf stars selected from catalogs based on the Gaia DR2 database reveal nine new gaseous debris disks that orbit single white dwarf stars, about a factor of two increase over the previously known sample. For each source we present gas emission lines identified and basic stellar parameters, including abundances for lines seen with low-resolution spectroscopy. Principle discoveries include: (1) the coolest white dwarf (T eff ≈12,720 K) with a gas disk; this star, WD01… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…This confirms that planet-planet scattering in multiple-planet systems naturally explains the newly discovered WD 1856 b orbiting in a 1.4 days period (Vanderburg et al 2020). Furthermore, these planets or asteroids can be influenced by tidal forces of the WD (Veras & Fuller 2019;Veras et al 2019) forming debris disks (Gänsicke et al 2006;Kilic & Redfield 2007;Farihi 2016;Wilson et al 2019), with some of them having gaseous components (Melis et al 2012;Manser et al 2016Manser et al , 2020Melis et al 2020); producing photo-evaporation of their atmospheres (Gänsicke et al 2019) or having the rocky bodies themselves (Vanderburg et al 2015;Manser et al 2019;Vanderbosch et al 2020) producing WD atmospheric pollution.…”
Section: Discussionsupporting
confidence: 58%
“…This confirms that planet-planet scattering in multiple-planet systems naturally explains the newly discovered WD 1856 b orbiting in a 1.4 days period (Vanderburg et al 2020). Furthermore, these planets or asteroids can be influenced by tidal forces of the WD (Veras & Fuller 2019;Veras et al 2019) forming debris disks (Gänsicke et al 2006;Kilic & Redfield 2007;Farihi 2016;Wilson et al 2019), with some of them having gaseous components (Melis et al 2012;Manser et al 2016Manser et al , 2020Melis et al 2020); producing photo-evaporation of their atmospheres (Gänsicke et al 2019) or having the rocky bodies themselves (Vanderburg et al 2015;Manser et al 2019;Vanderbosch et al 2020) producing WD atmospheric pollution.…”
Section: Discussionsupporting
confidence: 58%
“…This rare polluting element is extremely difficult to detect in hotter white dwarfs and could be the signpost of accretion of the crust of a planetary object (Hollands et al 2021). More discoveries related to planetary systems around white dwarfs enabled by Gaia included: WD J0914+1914, a peculiar white dwarf in the process of evaporating a Neptune-like exo-planet (Gänsicke et al 2019); and the 14 newly identified white dwarfs with gaseous debris from rocky planetesimals (Melis et al 2020;Dennihy et al 2020;Gentile Fusillo et al 2021), which brought the number of such systems known from seven to 21.…”
Section: Introductionmentioning
confidence: 99%
“…The low statistics involved currently make it difficult to speculate on the root cause that differentiates between these systems. We also note that in the time interval between the submission and revision of this manuscript, a couple of pre-prints (Dennihy et al 2020;Melis et al 2020) reported about ten more WD discs with gaseous emission. There is some overlap between the systems observed in these two pre-prints, but we mention these studies for completion.…”
Section: Disc Masses and Spatial Extentmentioning
confidence: 75%